Agronomic effectiveness of phosphates in "cerrado" soil - Goedert, Wenceslau J.; Lobato, Edson (Pesquisa Agropecuaria Brasileira, 2014)
Eleven phosphate sources were tested in a Dark Red Latosol (Haplustox). The performance of these materials was evaluated during four years, with the following crop sequence: wheat, soybean, soybean, rice. According to the results, the phosphate sources can be ordered in four groups of decreasing performances: a. Supertriple, Gafsa phosphate and Magnesian Thermalphosphate: b. IPT Thermalphosphate, Pirocaua, Florida and Tennessee phosphates; c. Patos de Minas, Araxá and Abaetá phosphate; d. Catalão phosphate. The results also indicated that the effectiveness of rock phosphates improved when the soil acidity was higher; however, crop performance depended on a balance of factors such as soil acidity, availability of phosphorus, and plant adaptation.